Mentalizing in improvisational music therapy. Issue 4 (8th August 2019) - Strehlow, Gitta; Hannibal, Niels
ABSTRACT: Introduction : The concept of mentalization has become increasingly widespread in the psychotherapy discourse. This article investigates three important questions in relation to music therapy and mentalization-based treatment: 1. How is mentalizing in a musical context (improvisation) different from mentalizing in a verbal context? 2. How do mentalization processes unfold in a musical context during improvisation? 3. Are there ways of responding in musical improvisation that can facilitate the ability to mentalize? Method s : We employed reflexive investigation using clinical examples to illustrate our understanding of how mentalizing unfolds in the process of music therapy practice. Results : We illustrate different ways that non-mentalizing can appear in musical improvisation and exemplify how musical improvisation can enhance the ability to mentalize. Discussion : We argue that it is possible to distinguish between mentalizing in a verbal or musical context even though there are similarities. We argue that the mind-set of the therapist is the single most important factor in facilitating mentalizing in music therapy.